2007
DOI: 10.1634/stemcells.2007-0197
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Mesenchymal Stem Cells: Their Phenotype, Differentiation Capacity, Immunological Features, and Potential for Homing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,663
0
87

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,152 publications
(1,777 citation statements)
references
References 126 publications
27
1,663
0
87
Order By: Relevance
“…[24] However, they are also capable of differentiating into nonmesenchymal cells like neural cells [25] under suitable conditions. Earlier, differentiation of hMSCs was tried and carried out by the addition of various growth factors in the culture media at different stages of growth or maturation.…”
Section: Growth Factor Delivery Via A8 Hydrogel Formed In Presence Anmentioning
confidence: 99%
“…[24] However, they are also capable of differentiating into nonmesenchymal cells like neural cells [25] under suitable conditions. Earlier, differentiation of hMSCs was tried and carried out by the addition of various growth factors in the culture media at different stages of growth or maturation.…”
Section: Growth Factor Delivery Via A8 Hydrogel Formed In Presence Anmentioning
confidence: 99%
“…5 MSCs can migrate to sites of tissue damage, 6,7 where they are activated by inflammatory cytokines (such as IFN-c) and several chemokines, which can recruit or suppress lymphocytes. [8][9][10][11] Interleukin-1b (IL-1b) is an important inflammatory factor that is expressed abundantly during the active phase of UC. [12][13][14] The UC mice induced by DSS treatment exhibit many symptoms similar to human UC, such as diarrhea, bloody feces, body weight loss, mucosal ulceration and shortening of the large intestine.…”
Section: Introductionmentioning
confidence: 99%
“…24 Other studies have shown that MSC transplantation into fetal or neonatal animals have resulted in the engraftment to different tissues without provoking an immune response. 25,26 Even though most of the MSC get trapped in the lungs after intravenous injection, evidence shows that MSC are capable of homing to the injured tissue after intravenous injection. Cultured rat and human MSC have been shown to migrate into the sites of brain injury after cerebral ischemia when transplanted intravenously in rats.…”
Section: Potential Clinical Application Of Mscmentioning
confidence: 99%